Meta Analisis: Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Media Terhadap Kemampuan Berpikir Kritis - Fitri Nazilatul Mukhlisoh; Iis Holisin; Febriana Kristanti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2023)
We have often heard of meta-analytical research related to the problem based learning model itself, but this time the researcher wants to examine the problem based learning model with its novelty form, namely in terms of the media used. This meta-analysis study was conducted with the aim of knowing the total effect size and analyzing the problem-based learning model assisted by media on critical thinking skills, where this meta-analysis research used 10 research articles from 980 scientific articles found on Harzing's Publish or Peerish platforms that meet exclusion and inclusion criteria. The results of the meta-analysis showed that the problem-based learning model with media-assisted learning on critical thinking skills did not have specific provisions in learning materials, but for its application it was more effective at the elementary level with the aid of concrete media as evidenced by a high effect size value of 1.042.